2016
DOI: 10.1136/heartjnl-2016-310112
|View full text |Cite
|
Sign up to set email alerts
|

Blood urea nitrogen-to-creatinine ratio in the general population and in patients with acute heart failure

Abstract: In patients with AHF, BUN/creatinine higher than age-specific and sex-specific normal range is associated with worse prognosis independently from both creatinine and BUN. CLINICAL TRIALS: gov identifier NCT00328692 and NCT00354458.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
83
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(92 citation statements)
references
References 32 publications
5
83
0
4
Order By: Relevance
“…As BUN and Cr are well-recognized biomarkers for estimation of kidney function and damage,[17] that performed in this study. Analysis of data by SPSS showed that statistically, there is no significant difference between the two groups receiving GELNs and the PBS group ( P > 0.05) [Figure 4].…”
Section: Resultsmentioning
confidence: 99%
“…As BUN and Cr are well-recognized biomarkers for estimation of kidney function and damage,[17] that performed in this study. Analysis of data by SPSS showed that statistically, there is no significant difference between the two groups receiving GELNs and the PBS group ( P > 0.05) [Figure 4].…”
Section: Resultsmentioning
confidence: 99%
“…Patients with elevated BUN/Cr were more prone to improve renal function during hospitalisation and to develop WRF after discharge 8. Intriguingly, in the work of Matsue et al 4 BUN/Cr was not related to inhospital WRF, a finding that could be explained by differences among characteristics of patients and criteria used to define WRF among studies 7 8…”
mentioning
confidence: 98%
“…In their Heart paper, Matsue et al ,4 evaluate the prognostic implications of the BUN to creatinine ratio (BUN/Cr) in a cohort of patients with AHF, using the normal values previously determined in a general population cohort. Indeed, an age-specific and sex-specific normal range of BUN/Cr was determined in a cohort of 4484 subjects with a mean age of 44±11 years, 55% women and most of them Caucasians.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, neurohormonal activity is reflected in the BUN/creatinine ratio which effectively ‘normalizes’ BUN for the degree of renal dysfunction, as measured by the creatinine level. To investigate the prognostic value of the BUN/creatinine ratio in AHF, Matsue and colleagues1 first defined age and sex specific normal ranges. Even in normal individuals, there is wide variation in the BUN/creatinine ratio, an increase with age, and higher levels in women compared to men.…”
mentioning
confidence: 99%